Offensive and defensive agility: A sex comparison of lower body kinematics and ground reaction forces - Spiteri, T.; Hart, N. H.; Nimphius, S. (Journal of Applied Biomechanics, 2014)
The aim of this study was to compare biomechanical and perceptual-cognitive variables between sexes during an offensive and defensive agility protocol. Twelve male and female (n = 24) recreational team sport athletes participated in this study, each performing 12 offensive and defensive agility trials (6 left, 6 right) changing direction in response to movements of a human stimulus. Three-dimensional motion, ground reaction force (GRF), and impulse data were recorded across plant phase for dominant leg change of direction (COD) movements, while timing gates and high-speed video captured decision time, total running time, and post COD stride velocity. Subjects also performed a unilateral isometric squat to determine lower body strength and limb dominance. Group (sex) by condition (2 × 2) MANOVAs with follow-up ANOVAs were conducted to examine differences between groups (P ? .05). Male athletes demonstrated significantly greater lower body strength, vertical braking force and impulse application, knee and spine flexion, and hip abduction, as well as faster decision time and post COD stride velocity during both agility conditions compared with females. Differences between offensive and defensive movements appear to be attributed to differences in decision time between sexes. This study demonstrates that biomechanical and perceptual-cognitive differences exist between sexes and within offensive and defensive agility movements.